ICT Policy Development and Implementation in South Africa: Towards an Improved E-Government Implementation - Mosehlana, M. B. (International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
The application of Information and Communication Technologies (ICTs) in government operations has become inevitable given an environment in which public administration find itself in the 21st century. South Africa is not immune to this environment and is required to continuously improve the use of ICTs in government administrations to fully reap the benefits of e-government. A progressive e-government requires a strong and robust ICT policy environment, however, the South African government has lacked behind between 2001 and 2015 in ensuring that the country continues to have an effective and up-to-date ICT policy that addresses the interconnected nature of the ICT environment. As a result, implementation of e-government in the country experienced a wide range of policy, leadership and administrative problems including outdated ICT policy framework, weak political leadership, lack of coordination and overlapping roles amongst institutional role players causing divisions and dubious transfer of power, poor management of the e-government portfolio, poor maintenance and preservation of ICT investments, concerns with IT training and skills development, lack of Public Private Partnerships in e-government, lack of societal ICT uptake due to skills and capacity shortages, which ultimately hindered e-government progress in the country. The establishment of a recently updated White Paper on National Integrated ICT Policy, 2016 provides better prospects and pave a way towards an improved e-government implementation in the country, which seeks to address these concerns. A number of considerations are essential in ensuring an improved implementation e-government implementation.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: E-government; ICT policy; policy implementation; South Africa; Information Communication Technology (ICT); ICT